1995
DOI: 10.1159/000236894
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Related Differences in the Tracheal Responsiveness of Sensitized Guinea Pig

Abstract: The purpose of this study was to evaluate the strain-related differences in tracheal hyperresponsiveness in control and egg albumen-sensitized guinea pigs. Concentration-response curves to acetylcholine and barium chloride were established from tracheal rings of Dunkin-Hartley and BEA strain guinea pigs. In the Dunkin-Hartley strain, sensitization did not signficantly increase the tracheal responsiveness to acetylcholine and barium chloride. By contrast, in the BFA strain, significant sensitization-induced hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We recently reported that the active sensitization of ileum and aorta [7]. Consequently, a common defect may guinea-pigs in vivo to egg albumen led to contractile occttr after sensitization in these dilTerent rnuscles, hyperresponsiveness in various muscles [1,2]. hi this…”
Section: Introductionmentioning
confidence: 91%
“…We recently reported that the active sensitization of ileum and aorta [7]. Consequently, a common defect may guinea-pigs in vivo to egg albumen led to contractile occttr after sensitization in these dilTerent rnuscles, hyperresponsiveness in various muscles [1,2]. hi this…”
Section: Introductionmentioning
confidence: 91%
“…Although the pathophysiological changes associated with antigen sensitization have not yet been clearly defined, a non-specific hyperresponsiveness is a characteristic feature that has been primarily detected in airways (Boushey, Holtzman, Sheller & Nadel, 1980). Until now, smooth muscle hyperresponsiveness occurring in allergic diseases and sensitized models has been mainly investigated in airways with special attention to the asthmatic disease (Saad & Burka, 1983;Morcillo, Perpina & Esplugues, 1984;Mansour & Daniel, 1987;Featherstone, Hutson, Holgate & Church, 1988;Kamm & Drazen, 1992;Bidon, Blin, Gogny, Vu & Jondet, 1995). We recently reported a lack of specificity in target organs for smooth muscle hyperreactivity that occurred in both vas deferens and ileum isolated from ovalbumen actively sensitized guinea-pigs (Bidon, Blin, Gogny, Vu & Jondet, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pascual et al (1993) showed that aortic rings became hyperreactive in a sensitized guinea-pig model. Sensitized smooth muscle has been shown to undergo non-specific alterations in mechanical properties, occurring prior to the specific antigen challenge (Morcillo et al, 1984;Ortiz et al, 1989Bidon et al, 1994Bidon et al, , 1995. This suggested that the essential defect in allergic hyperresponsiveness might be at the muscle cell level.…”
Section: Introductionmentioning
confidence: 99%